MANAGEMENT OF DYSTOCIA FOLLOWED BY UTERINE PROLAPSE IN MARES -A REPORT OF TWO CASES - HADIYA, K K; PARMAR, J J; DHAMI, A J; PATEL, J A; SHAH, A I (The Indian Journal of Animal Reproduction, 2023)
This communication puts on record the successful clinical management of dystocia due to stress inducedabortion in one mare and uterine inertia with overdue gestation in another using oxytocin and digitally inducedcervical dilation and forced extraction of fetus followed by uterine prolapse a few hours later in both the maresand their medical management.
Keywords: Mare; Dystocia; Uterine prolapse; Uterine inertia; Abortion; Medical management